The Use of Tps in EFL Classroom Activities to Reduce Situation Specific Speaking Anxiety in Delivering Ads Materials - Hidayat, Cece; Gaffar, Muhammad Andriana; Mulyanto, Agus; Wahyudi, Mustadim; Ismaurah, Nenden (Badan Pengembangan dan Pembinaan Bahasa, 2024)
The possible causes of situation-specific speaking anxiety include fear of making mistakes, lack of confidence, and anxiety about speaking in front of peers or the teacher. Teachers need to find effective strategies to help students reduce speaking anxiety. This study employed qualitative research with a case study method. The data was collected through observations, questionnaires, and interviews. The participants were 18 students from the 10th grade. Based on the research results, the Think-Pair-Share strategy can be used as one of the methods to reduce situation-specific speaking anxiety. The use of this strategy as a teaching method has helped students reduce their anxiety and therefore improve their speaking ability. Students' responses showed that this strategy can: (1) Increase self-confidence, (2) Reduce anxiety, (3) Improve oral communication skills, (4) Provide enjoyable activities, and (5) Increase students' motivation to speak English in class.